Improving Speaking Skills Through Role-Play of VII Grade Students of SMPN 2 Mamuju - Al-Azhari, St. Sarah; Munir, Munir; Azis, Jumrah (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This study aims to assess whether incorporating role play contributes to the enhancement of students' speaking abilities at SMPN 2 Mamuju. The independent variable considered is the utilization of role play, while the dependent variable is the speaking proficiency of the students. The research encompasses all seventh-grade students at SMPN 2 Mamuju, with Class VII.5, consisting of 32 students, selected as the sample using cluster random sampling. Data were gathered through scenarios presented in both pretest and posttest phases. Analytical techniques involved descriptive and inferential statistical methods. The data analysis reveals an observable improvement in students' speaking skills, with the average post-test score (86.40) surpassing the pre-test score (57.96). To sum up, the integration of role-playing has a beneficial impact on the speaking abilities of seventh-grade students at SMPN 2 Mamuju. Future research endeavors could explore how role-playing strategies might also enhance other skills, such as listening, reading, and writing.